E.P. Thompson, the Early New Left and the Fife Socialist League. Issue 1 (April 2016) - Efstathiou, Christos
Abstract : This article analyses the role of the early New Left, and especially Edward Palmer Thompson, in the formation and political development of the Fife Socialist League in the late 1950s and early 1960s. The focus is on the attempts of The New Reasoner group to become affiliated with the Fife Socialist League and its leader, Lawrence Daly. This article outlines how both The New Reasoner group and the League initially understood their dissident stance inside the British Communist camp. It places them in the historical context of the early British New Left and reveals how a New Leftist presence in the case of Fife was demonstrated in practice. The final section attempts to explain the reasons behind the limited influence of the New Leftists within the labour movement and how this affected the development of the League.